Pola Asuh dan Regulasi Emosi Siswa di SMA Negeri 1 Setu yang Kedua Orang Tuanya Bekerja - Resvany, Syafira; Abdillah, Rijal (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The time parents spend working causes a decrease in the quality of parenting and interaction and closeness between parents and children. This is a problem currently being faced by families, because busy work means parents' attention to their children is reduced, so parents have less time to educate their children, which results in reduced communication between parents and children. The abilities possessed by children can be obtained from the experiences of their parents, including the emotional regulation that parents have, of course it can influence the child's emotional regulation and parents can contribute to the development of children's emotional regulation by the way they care for them. This research aims to determine the relationship between parenting styles and emotional regulation in students at SMA Negeri 1 Setu whose parents both work. This research used quantitative research methods involving 224 research subjects of students in grades 10, 11 and 12 at SMA Negeri 1 Setu. Based on the results of the correlation test, the calculated significant value for authoritarian was 0.197, authoritative was 0.015, neglectful was 0.000, and indulgent was 0.106 with a correlation coefficient of -0.057, authoritative -0.146*, neglectful -0.225**, and indulgent - 0.084. Because the rule used is if the value (Ï) > 0.05 means that there is no relationship between authoritarian and indulgent parenting styles and emotional regulation in students at SMA Negeri 1 Setu whose parents both work.